Evaluation of multigrade teaching implementation at CLC SLDB Inandung TKB Punteh in Sabah, Malaysia - Hariri, Nur; Suhardi, Iwan; Syahrul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to evaluate the implementation of multigrade teaching at CLC SLDB Inandung TKB Punteh in Sabah, Malaysia, by employing the CIPP evaluation model (Context, Input, Process, Product). A qualitative approach was employed. Participants were selected through purposive sampling, involving teachers, students, and local stakeholders directly engaged in multigrade instruction. Participants were selected through purposive sampling, involving teachers, students, and local stakeholders directly engaged in multigrade instruction. The findings indicate that, in the context component, multigrade teaching is a strategic response to the educational needs of children of Indonesian migrant workers living in remote plantation areas. In the input component, teacher qualifications vary, and learning facilities remain limited, although strong teacher commitment supports instructional continuity. The process component reveals adaptive classroom management through integrated thematic instruction, flexible grouping, and time management despite limited instructional media. The product component shows positive impacts on access to education, learning motivation, attendance, and student character development, although academic achievement, particularly in literacy, numeracy, and basic technology use, still requires improvement. Based on these findings, strengthening teacher capacity and improving learning facilities are recommended to enhance the sustainability and quality of multigrade instruction in community-based education settings.